Clasp Together: Composing for Mind and Machine - Whalley, J. Harry; Mavros, Panagiotis; Furniss, Peter (Empirical Musicology Review, 2015)
This paper will explore questions of agency, control and interaction and the embodied nature of musical performance in relation to the use of human-computer interaction (HCI), through the experimental work Clasp Together (beta) [1] for small ensemble and live electronics by J. Harry Whalley. This practice-led research is situated at the intersection of music neurotechnology for sound synthesis and brain-computer interfaces (BCI, a subdomain of HCI), and explores the use of neural patterns from Electroencephalography (EEG) as a control instrument. The composition departed from the traditional composer/performer paradigm by using both non-instrumental physical gestures and cognitive or emotive instructions integrated into the score.